Pelatihan dan Pendampingan Usaha Bengkel Mobil Berbasis Added Value dalam Mewujudkan Sustainable Development Goals (SDGS) - Arif Susanto; Fitri Rahmawati; Widiyatmoko Widiyatmoko; Dwicky Ari Ariyanto (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2025)
The car repair shop business does not only rely on car maintenance services, but is supported by comfortable facilities and excellent service. The car repair shop "Samudra Auto Clinic 86" is a car repair shop business with a number of limitations, including limited types of service services, infrastructure, funding sources, and the ability to manage the workshop. The purpose of community service activities is to provide training in car service with injection technology, implementation of workshop administration systems, preparation of financial reports, marketing management, and occupational safety and health environmental management. The target subject of the activity is the car repair shop "Samudra Auto Clinic 86" located in Klaten Regency. The results of this community service activity are; 1) the application of new technology in car vehicle service, by adding types of services, namely offering car service services with injection technology so that partners can increase service competitiveness and remain existent amidst competition and can increase workshop income; and 2) availability of data on customers, employee data related to the payroll system and service transactions, supplier data, goods in the workshop, services performed, complaint transactions, service type transactions, employees, payment data, and workshop receipt data so that the workshop can implement good management. The “Samudra Auto Clinic 86” Car Workshop is expected to continue to provide HR training and development that will increase employee productivity and performance, thereby contributing to the stability and economic growth of the community so that it can realize the Sustainable Development Goals (SDGS).